TRANSFORMASI STRUKTUR SOSIAL DALAM PEMANFAATAN RPTRA DHARMA SUCI JAKARTA UTARA - Wahjudi, Sugeng (Jurnal Pengabdian dan Kewirausahaan, 2019)
The focus of RPTRA's activities reflects services for children and community services to become a community center that functions as a center of interaction and is used by all elements of society from various age groups. This research is an advanced stage of previous research on the relationship of RPTRA managers. The communication network that is built into the use of the RPTRA can be utilized for the development of institutional components that are socio-economic. By using Max Webber's instrumental rationality approach, this study can identify the social changes that have been formed. This study will provide a description relating to changes in knowledge, attitudes and actions of the people who use RPTRA. Changes that arise from individual RPTRA users (mothers) are driven by actions based on value orientation. Their actions involved in activities at RPTRA were not driven by instrumental orientation (to obtain economic benefits) or traditional orientation (because of tradition - driven by the authority structure) In general it can be concluded that RPTRA was able to take a good role. RPTRA is not a material space that distributes materials / materials to make a transformation of the social structure of society (change in social action). The results of the study indicate the formation of rationality in the use of RPTRA if it is associated with user social actions and program activities that put RPTRA as a center in building social relations for their local communities and social change. Keywords: RPTRA, communication network, social change, social actions.